Anaerobic endurance of young swimmers aged 12 years - Stachowicz, M.; Milde, K.; Janik, M. (Biomedical Human Kinetics, 2011)
Study aim: To assess the effects of swimming training on anaerobic endurance, swimming velocity and chest girth in children aged 12 years. Material and methods: Two groups of children aged 12 years were studied. Group S (14 boys and 6 girls) training swimming at a sport-oriented school 3 days a week, 90 min per session, and Group R (6 boys and 6 girls) engaged in competitive swimming for 4 years. Children from Group S were subjected twice (in September and in February) to a swimming test consisting of 6 bouts of swimming the 12.5-m distance, spaced by 30-s intermissions. Mean and maximum swimming velocities in the entire test were recorded together with their ratio (Performance Index, PI). In children from Group R the swimming velocity at one 12.5-distance was recorded. Results: Apart from somatic indices, significant increases over the 5-month training period were noted in mean swimming velocity in boys and girls (p<0.001) and in maximum velocity in boys (p<0.01). No significant changes were noted in the performance index or in heart rate. Conclusions: Performance index as a measure of anaerobic endurance may serve as a useful tool in assessing the adaptive performance changes in young swimmers.Conclusions: Performance index as a measure of anaerobic endurance may serve as a useful tool in assessing the adaptive performance changes in young swimmers.